Artificial crime analysis systems using computer simulations and geographic information systems - Liu, Lin 1965-; Eck ,John (Information Science Reference, 2008)
"This book discusses leading research on the use of computer simulation of crime patterns to reveal hidden processes of urban crimes, taking an interdisciplinary approach by combining criminology, computer simulation,and geographic information systems into one comprehensive resource"--Provided by publisher